Filling the maize basket supports crop diversity and quality of household diet in Malawi - Snapp, Sieglinde S.; Fisher, M. (Springer, 2015)
Food security and dietary quality are broadly supported development goals, yet few studies have addressed how agricultural subsidy policies and promotion of modern crop varieties impact smallholder farm production and household diet. Crop intensification through subsidies could have indirect impacts through gains/losses in income and purchasing power, as well as direct influences on local availability. An integrated household survey conducted multiple times in Malawi provided evidence-based insights into the complex interactions between agriculture and nutrition. The nationally representative dataset indicated that agricultural input subsidies did not preclude crop or dietary diversity. Two pathways of subsidy impact appeared to be operating: an association with diversified cropping for a direct influence on available food quality; and an association with adoption of modern maize varieties for an indirect influence through commercialization and income that supports diverse food purchases. Although crop diversity was positively associated with dietary diversity, we found that education, income, market access, and availability of improved storage technologies had higher influence on dietary diversity. Finally, we provide evidence supporting the need for complementary investments in both education and employment creation, particularly for female heads of households.